Influence of Solvothermal Temperatures and Times on Crystallinity and Morphology of MOF-5 - Tri Ana Mulyati; Ratna Ediati; Afifah Rosyidah (Indonesian Journal of Chemistry, 2015)
MOF-5 (metal-organic frameworks-5) have been synthesized using solvothermal method in which reaction mixtures of zinc nitrate hexahydrate and 1,4-benzenedicarboxylic acid (BDC) in dimethylformamide (DMF) were heated at various heating temperatures and times in order to observe the influence of heating temperature and time on crystallinity and morphology of the obtained MOF-5. The heating temperatures used were 105, 120 and 140 °C, respectively with heating times of 12–144 h. Determination of the best reaction conditionswas based on the observation of phase purity and crystal morphology of MOF-5 using XRD and SEM. The characterization results showed that MOF-5 crystals with a higher crystallinity were obtained when the reaction mixtures were heated at 105 °C for 144 h, 120 °C for 24 h or 140 °C for 12 h. The maximum weight of MOF-5 crystal was generated from reaction mixture heated at 120 °C for 72 h.